2006
DOI: 10.1111/j.1748-5827.2006.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective open pilot study on the use of ciclosporin for feline allergic skin disease

Abstract: Ciclosporin may be helpful in symptomatically treating signs of feline allergic skin disease. However, it is important to remember that ciclosporin is not licensed for use in cats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
55
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 23 publications
(30 reference statements)
3
55
0
2
Order By: Relevance
“…Ciclosporin treatment in cats has been associated with toxoplasmosis, 6,7 post‐transplant malignant neoplasia, 8,9 diarrhoea, 3,4 vomiting, hyperactivity, increased appetite, 4 anorexia 10 and gingival hyperplasia 11 . This is similar to dogs, in which gingival hyperplasia 12 and gastrointestinal (GI) upsets 13 have also been described.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Ciclosporin treatment in cats has been associated with toxoplasmosis, 6,7 post‐transplant malignant neoplasia, 8,9 diarrhoea, 3,4 vomiting, hyperactivity, increased appetite, 4 anorexia 10 and gingival hyperplasia 11 . This is similar to dogs, in which gingival hyperplasia 12 and gastrointestinal (GI) upsets 13 have also been described.…”
Section: Introductionmentioning
confidence: 91%
“…The use of ciclosporin is gaining acceptance for treatment of feline allergic dermatitis, as several studies and anecdotal reports have demonstrated efficacy and apparent safety 3,4 . The true safety of this drug is of concern, as only limited data are available that specifically address the adverse effects of ciclosporin in cats 5–7 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, CsA has been reported as an effective drug for the long-term management of pruritus in human and canine atopic dermatitis (AD) [10,11,22,30]. In addition, several clinical trials have revealed that CsA is also effective for controlling pruritus in feline skin diseases [21,34].…”
mentioning
confidence: 99%
“…Recently this cyclic oligopeptide, which is able to block the transcription of cytokine genes in activated T cells, is being increasingly used in veterinary medicine [4]. In veterinary medicine, cyclosporine has been reported to be effective for the treatment of a number of dermatologic diseases and ophthalmologic problems [4,10,11]. Recent reports [1,4] suggested that the cyclosporine is the effective therapeutic options for GME in dogs.…”
mentioning
confidence: 99%